Analisis Asesmen Diagnostik dan Asesmen Sumatif pada Materi Teks Puisi Rakyat Siswa Kelas VII SMP Negeri 14 Mataram - Suci Setiawati; Siti Rohana Hariana Intiana; Syaiful Musaddat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the forms and implementation of diagnostic assessment and summative assessment in Indonesian language learning on the topic of folk poetry texts for seventh-grade students at SMP Negeri 14 Mataram. This study employed a descriptive qualitative research design. Data were obtained through document studies and observations. The data sources included teaching modules or lesson plans (RPP) and classroom learning activities. The research focused on Indonesian language learning with the topic of folk poetry texts for seventh-grade students at SMP Negeri 14 Mataram, where assessment implementation has been applied since the 2022/2023 academic year. Based on the initial observation conducted on April 21, 2026, students showed relatively positive responses to cognitive diagnostic assessments because they were conducted at the beginning of the learning process and were not overly demanding, allowing students to demonstrate their initial abilities more comfortably. In contrast, students tended to be more serious during summative assessments because these were related to the learning outcomes they had achieved. However, several challenges were identified in the implementation process, including differences in students’ abilities and varying levels of learning motivation.